Depressed and Socioeconomically Disadvantaged Mothers’ Progression Into a Randomized Controlled Mobile Mental Health and Parenting Intervention: A Descriptive Examination Prior to and During COVID-19 - Baggett, Kathleen M.; Davis, Betsy; Mosley, Elizabeth A.; Miller, Katy; Leve, Craig; Feil, Edward G. (Frontiers in Psychology, 2021)
Infants of low-income and depressed mothers are at high risk for poor developmental outcomes. Early parenting mediates infant experiences from birth, and early intervention can support sensitive and responsive parent practices that optimize infant outcomes via promoting developmental competencies. However, low-income and depressed mothers experience substantial challenges to participating in early intervention. They also have extremely limited access to interventions targeting depression. Interventions targeting maternal depression and parent practices can improve maternal and infant outcomes. Mobile internet-based interventions overcome numerous barriers that low-resource mothers face in accessing home-based interventions. Pandemic-related stressors likely reduce family resources and exacerbate distress of already heavily-burdened mother-infant dyads. During crises such as the COVID-19 pandemic, evidence-based remote coaching interventions are paramount. This article reports on a mobile intervention for improving maternal mood and increasing parent practices that promote infant development. An ongoing randomized controlled trial study provided a unique opportunity to monitor progression from referral to intervention initiation between two groups of depressed mothers: those prior to the pandemic and during the pandemic. The study also examines mother and infant characteristics at baseline. The sample consisted primarily of Black mothers experiencing extreme poverty who self-referred to the study in a large southern city, which is one of the most income disparate in the U.S. Prior to the pandemic, 97% of study participants successfully progressed from consent to intervention, as compared to significantly fewer—86%— during the pandemic. Mother-infant dyads during COVID-19, as compared to those prior to COVID-19, displayed similar pre-intervention demographic characteristics and intrapersonal characteristics.